Faktor-Faktor Yang Mempengaruhi Rendahnya Kunjungan Antenatal Care Pertama (K1) Di Desa Durian Lingga Kecamatan Sei Bingai Kabupaten Langkat Tahun 2022 - Melya Rehlikansa; Eka Purnamasari; Siska Suci Triana Ginting; Ester Simanullang (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Pregnancy is a process experienced by women all over the world. The pregnancy period starts from conception until the birth of the fetus, the duration of pregnancy (normal is 280 days (40 weeks or 9 months 7 days). Antenatal care is a health visit given to the mother during pregnancy in accordance with the specified antenatal care service guidelines. Antenatal care visits are visits by pregnant women to a midwife or doctor as early as possible since they feel they are pregnant to receive antenatal care/services. factors influencing the low number of first Antenatal Care (K1) visits in Durian Lingga Village, Sei Bingai District, Langkat Regency in 2022. This type of research is analytical observational research using a cross sectional approach, namely to analyze the factors that influence the low number of first antenatal care visits. In this study, the population was all pregnant women who had passed the first trimester and were willing to be interviewed. The total population obtained was 89 people (K1) in Durian Lingga Village, Sei Bingai District, Langkat Regency in 2022. Conclusion: The rate of first antenatal care visits for pregnant women in Durian Lingga Village, Sei Bingai District, Langkat Regency in 2022 is 39 people (48.1%). The variables knowledge, education, attitude and parity are variables that are related to the first Antenatal Care (ANC) visit in Durian Lingga Village, Sei Bingai District, Langkat Regency in 2022. Age and attitude variables of health workers are variables that are not related to the first Antenatal Care (ANC) visit in Durian Lingga Village. Sei Bingai District, Langkat Regency in 2022.